2022
DOI: 10.1111/cas.15247
|View full text |Cite
|
Sign up to set email alerts
|

Enforced dual‐specificity tyrosine‐regulated kinase 2 expression by adenovirus‐mediated gene transfer inhibits tumor growth and metastasis of colorectal cancer

Abstract: Colorectal cancer is one of the most common gastrointestinal tumors with good outcomes; however, with distant metastasis, the outcomes are poor. Novel treatment methods are urgently needed. Our in vitro studies indicate that dual‐specificity tyrosine‐regulated kinase 2 (DYRK2) functions as a tumor suppressor in colorectal cancer by regulating cell survival, proliferation, and apoptosis induction. In addition, DYRK2 expression is decreased in tumor tissues compared to nontumor tissues in colorectal cancer, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…32 Therefore, DYRK2 may contribute to increased response rates and may be a key marker for these new treatments and potential therapeutic applications in the future. 18 In conclusion, we showed that DYRK2 expression was associated with chemosensitivity to 5-FU and oxaliplatin in p53 wild-type CRC cells. Routine preoperative measurements of the p53 status and DYRK2 expression may be useful for predicting patient sensitivity and in the selection of new therapeutic strategies for patients undergoing chemotherapy for CRC.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…32 Therefore, DYRK2 may contribute to increased response rates and may be a key marker for these new treatments and potential therapeutic applications in the future. 18 In conclusion, we showed that DYRK2 expression was associated with chemosensitivity to 5-FU and oxaliplatin in p53 wild-type CRC cells. Routine preoperative measurements of the p53 status and DYRK2 expression may be useful for predicting patient sensitivity and in the selection of new therapeutic strategies for patients undergoing chemotherapy for CRC.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study showed that DYRK2 induced p53‐regulated apoptosis‐inducing protein 1 expression and DNA damage‐triggered apoptosis in a p53‐Ser46 phosphorylation‐dependent manner 14 . Additionally, overexpression of DYRK2 in CRC cell lines using Ad‐DYRK2‐WT induced p53‐Ser46 phosphorylation 18 . Therefore, we initially examined the expression levels of p53‐Ser46 phosphorylation in parental and DYRK2‐KO cells under basal conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations